From Knowledge to Action: Assessing the Interplay Between Health Awareness and Scabies Prevention Among Islamic Boarding School Students - Kadir Hasani, Abdul; Kartika, Kartika; Arbaani Djuria, Syafrina; Dwi Ari Wibowo, Wahyu (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Scabies remains a health concern in pesantren due to close physical contact and shared facilities, which increase transmission risk. This study aimed to analyze the relationship between knowledge and attitudes and scabies prevention behavior among students at Pondok Pesantren Modern Daarul Abror. A cross-sectional design was employed, involving 126 students selected through total sampling. Data were collected using a validated and reliable questionnaire (Cronbach’s α > 0.70) and analyzed using descriptive statistics and Spearman correlation. Results showed that the majority of students were female (57.1%) and had resided in the dormitory for more than one year. Most students demonstrated adequate knowledge (74.2%; mean score 7.00 ± 2.02), adequate attitudes (79.0%; 21.63 ± 2.56), and adequate prevention behavior (71.4%; 28.35 ± 2.70). Correlation analysis revealed a significant positive association between knowledge and preventive behavior (r = 0.243; p = 0.006), as well as between attitudes and preventive behavior (r = 0.189; p = 0.034), whereas demographic factors showed no significant effect. These findings highlight that individual psychological factors play a more important role than demographic characteristics in shaping prevention behavior. Strengthening structured health education and promotion programs in pesantren is recommended to improve knowledge and foster positive attitudes toward scabies prevention.